Implementing and evaluating online advance care planning training in UK nursing homes during COVID-19: findings from the Necessary Discussions multi-site case study project - Emily Cousins (BMC Geriatrics, 2022)
Abstract Background Advance care planning in nursing homes is important to ensure the wishes and preferences of residents are recorded, especially during the COVID-19 pandemic. However, care staff and family members frequently report feeling unprepared for these conversations. More resources are needed to support them with these necessary discussions. This research aimed to develop, implement and evaluate a website intervention for care staff and family members to provide training and information about advance care planning during COVID-19. Methods The research was a primarily qualitative case study design, comprising multiple UK nursing home cases. Data collection included semi-structured interviews with care staff and family members which were coded and analysed thematically. A narrative synthesis was produced for each case, culminating in a thematic cross-case analysis of the total findings. Theoretical propositions were refined throughout the research. Results Eight nursing homes took part in the study, involving 35 care staff and 19 family members. Findings were reported according to the RE-AIM framework which identified the reach, effectiveness, adoption, implementation and maintenance of the intervention. Themes included: website content that was well received; suggestions for improvement; implementation barriers and facilitators; examples of organisational and personal impact. Conclusions Four theoretical propositions relating to advance care planning in nursing homes are presented, relating to: training and information needs, accessibility, context, and encouraging conversations. Implications for practice and training include an awareness of diverse learning styles, re-enforcing the right to be involved in advance care planning and encouraging opportunities for facilitated discussion. Trial registration ISRCTN registry (ID 18003630 ) on 19.05.21.